Intelligent Character Students Formation As The Next Generation: Edition of The Implications Citizenship Education As Legal Studies - Oktavriana, Diah Ratri (International Conference on Islamic Studies, 2021)
The university as an educational institution has a role in the intellectual life of the nation and state. The role of the university as an educational institution is how to build the character of students, so that the purpose of character education for universities, namely encouraging the birth of ethical, personality, honest, intelligent, and tough people can be realized. Therefore, the cultivation and process of character building must be considered by a university. The way that can be done is by giving courses that can build student character, one of which is by giving citizenship courses. Through the provision of citizenship courses, it is hoped that the concept of citizenship which focuses on the formation of a diverse self in terms of religion, sociocultural, language, age and ethnicity, to become Indonesian citizens who are intelligent, skilled, and with character, in accordance with what is mandated by Pancasila. and the 1945 Constitution of the Republic of Indonesia. Thus, the focus of this paper is: first, regarding the curriculum material in the civics learning plan to support the character building of students as the younger generation. The second is planning a civics learning program to create intelligent characters for students as the younger generation.The research method used is a literature study method by reviewing library sheets from various criteria ranging from books, journals or articles. Literature research itself emphasizes the efforts of researchers in using sources in a professional and observant way from making research notes to bibliographies.